Effect of Cutting Conditions on the Size of Dust Particles Generated during Milling of Carbon Fibre-Reinforced Composite Materials - Dvořáčková, Štěpánka; Kroisová, Dora; Knápek, Tomáš; Váňa, Martin (Polymers, 2024)
Conventional dry machining (without process media) of carbon fibre composite materials (CFRP) produces tiny chips/dust particles that float in the air and cause health hazards to the machining operator. The present study investigates the effect of cutting conditions (cutting speed, feed per tooth and depth of cut) during CFRP milling on the size, shape and amount of harmful dust particles. For the present study, one type of cutting tool (CVD diamond-coated carbide) was used directly for machining CFRP. The analysis of harmful dust particles was carried out on a Tescan Mira 3 (Tescan, Brno, Czech Republic) scanning electron microscope and a Keyence VK-X 1000 (Keyence, Itasca, IL, USA) confocal microscope. The results show that with the combination of higher feed per tooth (mm) and lower cutting speed, for specific CFRP materials, the size and shape of harmful dust particles is reduced. Particles ranging in size from 2.2 to 99 μm were deposited on the filters. Smaller particles were retained on the tool body (1.7 to 40 μm). Similar particle sizes were deposited on the machine and in the work area.
Keywords: milling; CFRP; dust particles; electron microscopy; respiratory hazards